Human Metapneumovirus Induces Mucin 19 Which Contributes to Viral Pathogenesis - Kaitlin McBride; Ma. del Rocio Banos-Lara; Nagarjuna R. Cheemarla; Antonieta Guerrero-Plata (Pathogens, 2020)
Human Metapneumovirus (HMPV) remains one of the most common viral infections causing acute respiratory tract infections, especially in young children, elderly, and immunocompromised populations. Clinical symptoms can range from mild respiratory symptoms to severe bronchiolitis and pneumonia. The production of mucus is a common feature during HMPV infection, but its contribution to HMPV-induced pathogenesis and immune response is largely unknown. Mucins are a major component of mucus and they could have an impact on how the host responds to infections. Using an in vitro system and a mouse model of infection, we identified that Mucin 19 is predominantly expressed in the respiratory tract upon HMPV infection. Moreover, the lack of Muc19 led to an improved disease, lower lung viral titers and a decrease in the number of CD4+ T cells. These data indicate that mucin 19 contributes to the activation of the immune response to HMPV and to HMPV-induced pathogenesis.